2019
DOI: 10.1038/s41598-019-44828-6
|View full text |Cite
|
Sign up to set email alerts
|

ELK3 expressed in lymphatic endothelial cells promotes breast cancer progression and metastasis through exosomal miRNAs

Abstract: Tumor-associated lymphatic vessels (LV) serve as a route of cancer dissemination through the prometastatic crosstalk between lymphatic endothelial cells (LECs) lining the LVs and cancer cells. Compared to blood endothelial cell-derived angiocrine factors, however, LEC-secreted factors in the tumor microenvironment and their roles in tumor metastasis are poorly understood. Here, we report that ELK3 expressed in LECs contributes to the dissemination of cancer cells during tumor growth by providing oncogenic miRN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 32 publications
0
30
0
Order By: Relevance
“…Briefly, EXO and IDEM were loaded on a 96-well plate provided by the company and the CD63 positive particle number was quantified against a pre-set exosomes standard curve. The number of CD63+ particles obtained was then compared to the total amount of particles (quantified by NTA) to gather the amount of CD63+ particles out of the total (Kim et al, 2019). The percentage of EXO and IDEM presenting the exosomal surface markers CD81 was determined by flow cytometry.…”
Section: Evaluation Of Exosome-associated Markersmentioning
confidence: 99%
“…Briefly, EXO and IDEM were loaded on a 96-well plate provided by the company and the CD63 positive particle number was quantified against a pre-set exosomes standard curve. The number of CD63+ particles obtained was then compared to the total amount of particles (quantified by NTA) to gather the amount of CD63+ particles out of the total (Kim et al, 2019). The percentage of EXO and IDEM presenting the exosomal surface markers CD81 was determined by flow cytometry.…”
Section: Evaluation Of Exosome-associated Markersmentioning
confidence: 99%
“…This extensive study revealed that miR-1910-3p, contained in TNBC and ER- and PR-positive breast cancer cells, inhibited MTMR3, subsequently activating the NF-κB signaling pathway. Interestingly, tumor-associated lymphatic vessels contributed to increased invasion and migration by secreting exosomes containing miR-503-3p, -4269, and 30e-3p in TNBC cells [ 124 ]. All three exosomal miRNAs were identified as targets of ELK3, an ETS domain-containing protein with both transcriptional activation and repression capabilities downstream of the ERK1/2 and Ras signaling pathways.…”
Section: Roles Of Exosomal Micrornas In Breast Cancer Metastasismentioning
confidence: 99%
“…Moreover, the current work proved that ELK3 was a direct target of miR-3612, and LINC01116 could promote the expression of ELK3 by absorbing miR-3612 in BCa cells. According to previous reporters, ELK3 was closely associated with the development of breast cancer 34,35 , liver cancer 36 , colorectal cancer 37 , and prostate cancer 38 . In our study, we confirmed that ELK3 knockdown could markedly suppress cell growth and metastasis in BCa.…”
Section: Discussionmentioning
confidence: 90%